Analisis Ritual Perang Pandan Berbasis Perspektif Diakronis di Desa Wisata Tenganan Pegringsingan - Artadi, I Komang Agus Moni; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2019)
Tenganan Pegringsingan Village Tourism is located in Karangasem Regency, which has many ancestral cultures and traditions that are still held today. One of the famous traditions of the Tenganan Pegringsingan Village Tourism is the tradition perang pandan (Mekare - kare). Perang pandan has its own uniqueness that can only be found in Tenganan Village, from this uniqueness that makes many tourists who visit the Tenganan Pegringsingan Village Tourism just to witness the uniqueness of the perang pandan ritual. This study sought to find diachronic developments in the implementation of the perang pandan ritual, before and after the establishment of Tenganan Pegringsingan Village into a Village Tourism, using the over-time comparative method. The results of this study indicate, first seen from the indicator of time, participants who followed the tradition of the perang pandan ritual experienced a change. Secondly seen from the room indicator, the implementation of the perang pandan ritual is still permanent, cannot be changed. Third, judging from the level indicator, the perang pandan ritual has begun to move to a more complex level than before. and the last seen from the composite indicator, time, space and level, the perang pandan ritual has begun to be packaged into a tourist attraction, in the form of a festival tenganan that is routinely carried out every year. Keywords: Perang pandan, Diachronic Perspective. Village Tourism